Vertical trend of trace metals deposition in sediment core off Tanjung Pelepas harbour, Malaysia - Yusoff, Abdul Hafidz; Zulkifli, Syaizwan Zahmir; Ismail, Ahmad; Mohamed, Che Abd Rahim (Elsevier, 2015)
Sediment core collected from Tanjung Pelepas harbour was analyzed to determine the concentrations of trace metals e.g., Al, Fe, Ti, Pb, Zn, Cu and natural radionuclide 210Pb. The aim of this study was to predict the origin of trace metals and date the deposition of sediment that occurred at Tanjung Pelepas harbour using the vertical profile of 210Pb. The estimated sedimentation rate derived from 210Pb profile was 0.57 cm/year. The entire datasets of trace metals were analyzed statistically using the Pearson correlation coefficient and principal component analysis (PCA) to predict their origins. The results showed that Al, Fe and Ti originated from natural sources while Zn and Cu came mainly from anthropogenic sources. Pb was dominated with both anthropogenic and natural sources. The enrichment factors (EF) were also calculated to estimate the level of contamination. The EF indicated that Tanjung Pelepas harbour is considered to have minor enrichment (EF<3) of Pb, Zn and Cu. Historical variations of Zn and Cu show the highest EF values estimated in late 1990's when the harbour was being developed. The EF values of Zn and Cu increased slightly from the past to the recent years which may correlate to the increased development at the harbour area.